3,3′,5,5′-Tetra-tert-butyl-2′-hydroxy-[1,1′-biphenyl]-2-yl 4-methylbenzenesulfonate - Jian, Chunli (International Union of Crystallography, 2013)
In the title molecule, C(37)H(48)O(4)S, the benzene rings in the biphenyl fragment are inclined to each other at 61.1 (1)°. The hydroxy group is involved in a weak intramolecular O—H⋯O(sulfonate) hydrogen bond. One tert-butyl group is disodered over two orientations in a 0.682 (17):0.318 (17) ratio. In the crystal, weak C—H⋯O hydrogen bonds link the molecules into columns in direction [100].